Seleksi Progeni F1 Hasil Persilangan 2009 Berdasarkan Karakteristik Penghasil Lateks Dan Penghasil Kayu Pada Tanaman Karet (Hevea brassiliensis Muell. Arg.) - Sigit Aditya; Revandi iskandar M. Damanik; Mbue Kata Bangun (Jurnal Agroekoteknologi, 2015)
The research was conducted at The Rubber Research Center, Sungei Putih, Galang district, Deli Serdang region, North Sumatera with 54 metre altitude from February to July 2014. The aim of the research was to obtasin the highest potential progeny based on the latex and wood production which crossed in 2009. The parameters observed were: coefficient of covariance, corellation, regression of the selection with 1% and 10% intensity. From the result showed there were 54 progenies 4 years old used as the object. There were 5 progenies obtained in the selection on the latex yield with 10% intensity and 2 progenies with 1% (i.e. no.60: 11,76 g/p/s; no.44: 16,50 g/p/s) whereas in timber progenies there were 4 progenies with 10% selection intensity and 2 progenies (no.43: 1,59 m³/ph and no.99: 0,86 m³/ph) with 1% selection intensity.Keywords : Hevea brassiliensis, hasil persilangan seleksi, progeni.